Enhancing soil carbon and rice dry biomass with microbial fuel cells, optimal spacing, and fertilizer in rice fields - SHOFIE RINDI NURHUTAMI; SUDADI SUDADI; KOMARIAH KOMARIAH; WIDYATMANI SIH DEWI; ADHIA AZHAR FAUZAN (Society for Indonesian Biodiversity, 2024)
Abstract. Nurhutami SR, Sudadi, Komariah, Dewi WS, Fauzan AA. 2024. Enhancing soil carbon and rice dry biomass with microbial fuel cells, optimal spacing, and fertilizer in rice fields. Biodiversitas 25: 3331-3338. Microbial fuel cell (MFC) uses electroactive anode bacteria to compete in rice fields without disrupting cultivation or altering diversity. Therefore, this research aimed to explore the combination of MFC, different spacing methods (Jajarlegowo and conventional), and NPK (Nitrogen, Phosphorus, and Potassium) fertilizer affecting soil carbon dynamics and rice dry biomass. The key parameters included bacterial community, soil respiration, microbial biomass carbon, Soil Organic Carbon (SOC), Carbon to Nitrogen (CN) Ratio, and rice dry biomass. The results showed that there were no significant differences across the parameters when combined. However, MFC increased soil respiration (0.618 CO2.day-1) and microbial biomass carbon (0.121 ?g. g-1) but decreased SOC and rice dry biomass (0.039% and 3.978 g. clump-1). Jajarlegowo plant spacing enhanced soil respiration (0.583 CO2.day-1), microbial biomass carbon (0.122 ?g. g-1), and rice dry biomass (10.635 g. clump-1). Meanwhile, NPK fertilizer enhanced microbial biomass carbon (0.170 ?g. g-1), soil respiration (0.615 CO2.day-1), and rice dry biomass (5.993 g.clump-1) but lowered CN Ratio by 3.471. A positive correlation was also observed between soil carbon and rice dry biomass. These emphasized the need for a holistic method to develop MFC technology in rice paddy soils. Further research was suggested on the role of Electroactive Anodes Bacteria (EAB) in organic matter decomposition over multiple rice growing seasons.